PENGARUH LATIHAN SHOOTING MENGGUNAKAN TARGET AREA TERHADAP AKURASI TEMBAKAN ATLET SEKOLAH SEPAK BOLA (SSB) BATUKARANG PADA KELOMPOK USIA 13-15 TAHUN 2025 - Brendy S Tarigan; Julius Boy Nesra Basgimata Barus; Deasyi Natalia Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of shooting training using target areas on the shooting accuracy of Batukarang Football School (SSB) athletes in the 13-15 age group. This study was conducted at Batukarang Football School (SSB), Payung District, Karo Regency, North Sumatra, from October to November 2025. The method used was an experimental study with a pre-test and post-test control group design. The study sample consisted of 20 athletes selected using a purposive sampling technique. The research instrument used a shooting accuracy test consisting of 10 kicks with a maximum score of 30 points. The results showed that the average pre-test score was 15.1, which is in the sufficient category, while the average post-test score was 22.4, which is in the good category. An average increase of 7.3 points was observed after six weeks of training, performed three times per week. The statistical test using the t-test showed that the calculated t-value was greater than the table t-value, thus accepting the alternative hypothesis (Ha). Therefore, it can be concluded that there is a significant effect of shooting training using area targets on improving shooting accuracy in Batukarang SSB athletes aged 13–15 years. Shooting training using area targets has been proven effective in improving shooting accuracy, concentration, and mastery of basic techniques. Therefore, this training method is recommended for continuous implementation in youth soccer development programs to improve athlete technique and performance.